Assessment of current water, sanitation, and hygiene (WASH) practices in the third and ninth districts of N'Djamena, Chad - Daniel Mangueina; Esi Awuah; Mathias Fru Fonteh; Prince Antwi-Agyei; Emmanuel Tao Nadji (IWA Publishing, 2024)
Access to safe drinking water, sanitation, and hygiene in Chad's cities, especially N'Djamena, is a persistent and significant challenge. This study aimed to assess current practices in water, sanitation, and hygiene in N'Djamena's third and ninth districts. We surveyed 395 households, conducted water source identification, and analyzed seven water samples at the National Water Laboratory. Temperature, ammonium, total coliforms, and aerobic flora values exceeded World Health Organization (WHO) guidelines. Ammonium and temperature averaged 0.7 mg/L and 30.1-31.93 °C, respectively. Bacterial contamination (>100 MPN/100 mL) exceeded the WHO's 0 MPN/100 mL guidelines, rendering the water unfit for consumption. Survey results indicate that 78.7% use hand pumps, 21.1% have tap water access, and 0.2% rely on rivers for water. Regarding toilets, 92.8% have traditional models, 2.9% have modern facilities, and 4.3% practice open defecation. 95% dispose of untreated wastewater into nature, with only 5% using septic tanks. For solid waste, 72% use illegal dumpsites, 18% rely on public services, and 10% burn waste. Finally, 95.5% of households wash their hands with clean water and soap after using the toilet. It is crucial to treat drinking water and implement proper hygiene and sanitation measures to safeguard the population's health in the studied area. HIGHLIGHTS Identification of gaps for targeted interventions.; Enhancement of public health and quality of life.; Information for more effective WASH policies and programs.; Foundation for mobilizing resources and partnerships.; Strengthening resilience in the face of water-related challenges.;